2023
DOI: 10.1039/d3fo01226c
|View full text |Cite
|
Sign up to set email alerts
|

The alleviating effect of ellagic acid on DSS-induced colitis via regulating gut microbiomes and gene expression of colonic epithelial cells

Abstract: The anti-inflammatory effect of ellagic acid (EA) and its possible underlying mechanism in dextran sulfate sodium (DSS)-induced mouse chronic colonic inflammation were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Overall, findings suggest that the lacto-fermentation of herbal infusions could enhance their antioxidant and anti-inflammatory effects, and this effect could be explained, at least partly, by the increase in and release of their phenolic fractions. Although no individual phenolics were evaluated, previous preclinical studies have found both antioxidant and anti-inflammatory activities in the gastrointestinal tract for many, such as rosmarinic acid, ellagic acid, chicoric acid, and caffeic acid, which are present in significant amounts in these herbs and plant extracts [51][52][53][54]. Furthermore, in order to explain whether the effect could be mediated by the (poly)phenolics, we ran a Pearson correlation analysis to evaluate a potential statistical correlation between the changes in the (poly)phenolics through lactofermentation and the antioxidant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, findings suggest that the lacto-fermentation of herbal infusions could enhance their antioxidant and anti-inflammatory effects, and this effect could be explained, at least partly, by the increase in and release of their phenolic fractions. Although no individual phenolics were evaluated, previous preclinical studies have found both antioxidant and anti-inflammatory activities in the gastrointestinal tract for many, such as rosmarinic acid, ellagic acid, chicoric acid, and caffeic acid, which are present in significant amounts in these herbs and plant extracts [51][52][53][54]. Furthermore, in order to explain whether the effect could be mediated by the (poly)phenolics, we ran a Pearson correlation analysis to evaluate a potential statistical correlation between the changes in the (poly)phenolics through lactofermentation and the antioxidant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) represents an idiopathic chronic, relapsing inflammatory disorder in the intestines that is caused by dysregulation of the mucosal immune system [36]. Dietary factors are known to influence the composition and abundance of gut microbiome and have the potential to shape the interplay between gut microbiome and immune responses involved in the pathogenesis of IBD [37,38] and many other diseases. Dietary factors, including bacterial products and gut-derived metabolites, such as short-chain fatty acids, can affect the colonization of certain gut microorganisms [39,40] and gut permeability changes.…”
Section: Discussionmentioning
confidence: 99%